2019
DOI: 10.1097/rhu.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eosinophilic Granulomatosis With Polyangiitis and Associated Health Care Utilization Among Patients With Concomitant Asthma in US Commercial Claims Database

Abstract: Objective To estimate the prevalence and associated disease burden of eosinophilic granulomatosis with polyangiitis (EGPA) in patients with asthma from a US claims database. Methods Two cohorts were defined using enrollees (aged ≥18 years) from the Optum deidentified Clinformatics Datamart claims database 2010–2014, based on validated EGPA case definitions with varying specificity: EGPA 1 (main cohort; more specific; patients with 2 codes [in any combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
7
20
3
1
Order By: Relevance
“…It was therefore not feasible to reliably evaluate potential trends in incidence or prevalence. A large real-world database study published after the time period of this systematic literature review has shown that in the USA, EGPA is more common in females than in males and more frequently reported in individuals over 50 years of age [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore not feasible to reliably evaluate potential trends in incidence or prevalence. A large real-world database study published after the time period of this systematic literature review has shown that in the USA, EGPA is more common in females than in males and more frequently reported in individuals over 50 years of age [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, a specific diagnosis code for use in identifying patients with EGPA from health records was only established in the United States in October 2015 with the adoption of the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM); before ICD-10-CM, studies evaluating the burden of EGPA via retrospective analyses of administrative claims data relied on a series of coding algorithms (eg, International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] diagnosis and procedures codes, Current Procedural Terminology [CPT] codes, and physician specialties). [13][14][15][16][17][18] Owing to the previous lack of EGPA-specific diagnosis codes and limited number of regulatory approved treatments, data are limited on the clinical and economic burden of EGPA. Comparing clinical outcomes in EGPA with those in patients with asthma, in which the disease burden is well established, 19 is a useful way to measure the burden of EGPA for patients and payers.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Historically, conventional treatment was with OCS, with or without additional immunosuppressive drugs, 59 but many patients experienced corticosteroid‐related side effects or relapses during OCS tapering 60 . As a result, healthcare resource utilization and burden of disease and treatment were high 61 …”
Section: Mepolizumab Treatment In the Rare Disease Eosinophilic Granu...mentioning
confidence: 99%
“…60 As a result, healthcare resource utilization and burden of disease and treatment were high. 61 Since eosinophils contribute to the pathophysiology of EGPA, and with severe eosinophilic asthma being a key feature of the disease, 57 mepolizumab was postulated as a potential treatment option for patients with EGPA. In 2010, early data on the use of mepolizumab in patients with EGPA were published in a case report and in a pilot trial.…”
Section: Mep Olizumab Tre Atment In the R Are D Is E A S E Eos Inophi...mentioning
confidence: 99%